PENERAPAN WEB INVENTORY UNTUK PENGELOLAAN STOK SERAGAM SEKOLAH PADA UKM STAR PURNAMA - Endra Rahmawati; Muhammad Rafly Ardiansyah; Muhammad Farid Alif Prasetyo; Daffa Tyan Putro (Batara Wisnu : Indonesian Journal of Community Services, 2023)
UKM Star Purnama is one of the Small and Medium Enterprises in the North Surabaya area which is engaged in selling school uniforms. UKM Star Purnama has 1 shop and 1 warehouse for stocking school uniforms. However, there are often discrepancies in the number of school uniform stocks in the shop owner's records and the actual goods in the warehouse. This causes the owner to have difficulty in managing the number of orders received from customers. Apart from that, data collection must be carried out repeatedly to ensure that the stock amount in the owner's notebook and the real stock amount are the same as those in the warehouse. To overcome this problem, an inventory recording system is needed to make it easier for warehouse owners and employees to monitor incoming and outgoing stock during a certain period. The creation of this inventory application will be followed by training for the owner and a number of employees regarding the implementation of the application system. In training activities, owners and employees have been given insight into the application features and the types of reports that can be generated from the application. The results of the training showed that there was a change in the work system of owners and employees who switched to using a web-based inventory application and the suitability of the number of school uniform stock records in the application compared to the number of stocks in the warehouse was the same